A review of ICT-based applications to monitor environmental parameters. Issue 1 (6th January 2020) - Habibi, Shahryar
Abstract : Purpose: The purpose of this study is to implement environmental control systems; information and communication technologies based on user behavior for smart buildings and describe their definitions, technological advances, advantages and modern uses. It also highlights the complexity and difficulty of energy management and comfort via control devices. Design/methodology/approach: This study reviews recent progress in control, information technologies, sensing and optimization in buildings and addresses the automation and environmental control systems of important parameters such as lighting, noise, temperature and humidity. It also explores the technological innovations and methods of management through sensors based on user behavior for the processes of optimization and control. Findings: A proposed prototype has been developed by the combination of user behavior and control systems in buildings, mainly related to thermal comfort and energy use. This study addresses the development of a smart-comfort control system based on users' behavior. Originality/value: The main contribution of this study is the goal-driven development of an indoor quality apparatus for environmental monitoring data by using smart sensor systems. It can help users to monitor and control their environmental factors and provides functionalities for assessing comfortable ranges.